The Analysis of Speech Act of Tourism Promotion in Pesona Indonesia and Malaysia Truly Asia: A Cross-Cultural Pragmatic Study - Ikhsan Al Izyra; Ni Wayan Sartini (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This study aims to analyze the illocutionary speech act used in the promotion of rural tourism in high-altitude areas by the Indonesian and Malaysian Ministries of Tourism. Searle's taxonomy of illocutionary speech acts (1979) is used, namely assertive, directive, commissive, expressive and declarative to categorize rural tourism. The data in this study were taken from the YouTube platform which was published in 2022 with the theme of video content promoting of rural tourism in high-altitude. Data analysis through Searle's taxonomy which is interpreted through a qualitative descriptive method. The results of the study found that there were similarities found, namely the types of assertive, directive and expressive illocutionary acts in PI and MTA. Meanwhile, commissive and declarative types were not found in both. Overall, a total of 58 utterances were obtained, including illocutionary speech acts in PI found a total of 32 utterance frequencies and MTA a total of 26 utterance frequencies. Cross-culturally, MTA in promoting its tourism is accompanied by criticizing developments that have a negative impact on tourist villages. Meanwhile, PI in promoting its tourism prioritizes providing information and cultural knowledge to listeners.